Long non‐coding RNAs with low expression levels in cells are enriched in secreted exosomes. (13th May 2014) - Gezer, Ugur; Özgür, Emre; Cetinkaya, Merve; Isin, Mustafa; Dalay, Nejat
Abstract Long non‐coding RNAs (lncRNAs) are involved in regulating chromatin modifications, gene transcription, mRNA translation, and protein function. We recently reported a high variation in the basal expression levels of a panel of lncRNAs in HeLa and MCF‐7 cells and their differential response to DNA damage induction. Here, we hypothesized that lncRNA molecules with different cellular expression may have a differential abundance in secreted exosomes, and their exosome levels would reflect cellular response to DNA damage. MALAT1, HOTAIR, lincRNA‐p21, GAS5, TUG1, CCND1‐ncRNA in exosomes secreted from cultured cells were characterized. A different expression pattern of lncRNAs in exosomes was seen compared to cells. RNA molecules with relative low expression levels (lincRNA‐p21, HOTAIR, ncRNA‐CCND1) were highly enriched in exosomes. TUG1 and GAS5 levels were moderately elevated in exosomes, whereas MALAT1—which was the most abundant molecule in cells—was present at levels comparable to its cellular levels. lincRNA‐p21 and ncRNA‐CCND1 were the main molecules; exosome levels of them best reflect the change of their cellular levels upon exposure of the cells to bleomycin‐induced DNA damage. In conclusion, we provide evidence that lncRNAs have a differential abundance in exosomes, indicating a selective loading.